Physiological Basis of Water Stress Tolerance in Soybean (Bangladesh Agronomy Journal, 2016)
An experiment was conducted to study the effects of water stress on physiological parameters associated to drought tolerance in soybean at the Department of Agronomy, Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur, Bangladesh during January to April, 2015. Four soybean genotypes namely i) BU Soybean 1 ii) Binasoybean 1 iii) Galarsum and iv) BARI Soybean 5 were grown in two watering regimes viz. control (80% of the field capacity) and water stress (50% of the field capacity). Genotypic variability was found in water stress tolerance in soybean. Highest accumulation of leaf proline, sugar and water content and lower accumulation of malondialdehyde were found in Binasoybean 1 compared to other genotypes. Lowest yield reduction was found in Binasoybean 1. Binasoybean 1 showed relatively higher drought tolerance whereas BARI Soybean 5 was found susceptible to yield. It was found that higher water stress tolerance in Binasoybean 1 was associated with better water relations and higher accumulation of sugar and proline and lower accumulation of malondialdehyde content in leaf.Bangladesh Agron. J. 2015, 18(2): 71-78